Pelaksanaan Layanan Bimbingan dan Konseling di MI Al Ittihadiyah Jakarta Barat - Rahmawati Al-Nur, Widya; Wardana, Alya; Luqyana , Anggun; Amalia, Rizki (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2025)
This study aims to examine the implementation of Guidance and Counseling (BK) services in Madrasah Ibtidaiyah (MI) Al-Ittihadiyah West Jakarta. BK services in elementary schools have an important role in supporting student development, both in personal, social and academic aspects. This research uses a qualitative approach with a case study method, where data is collected through observation and structured interviews with homerooms 2 and 4. The results showed that the counseling program at MI Al-Ittihadiyah has been running since 2024 and is handled by the respective homerooms. However, limited time and resources are the main obstacles in optimizing these services. Homeroom teachers use persuasive and motivational approaches to help students overcome problems such as fighting, teasing, and academic difficulties. Nonetheless, the effectiveness of BK services is still hampered by the lack of focus and time allocated for counseling. This study recommends BK training for homeroom teachers, integration of BK services with the school management information system, periodic evaluation, and the placement of a dedicated BK teacher to improve the quality of services. Thus, BK services are expected to be more effective in supporting students' development and creating a conducive school environment.